Discovery of Alpha-Gal-Containing Antigens in North American Tick Species Believed to Induce Red Meat Allergy - Crispell, Gary; Commins, Scott P.; Archer-Hartman, Stephanie A.; Choudhary, Shailesh; Dharmarajan, Guha; Azadi, Parastoo; Karim, Shahid (Frontiers in Immunology, 2019)
Development of specific IgE antibodies to the oligosaccharide galactose-α-1, 3-galactose (α-gal) following tick bites has been shown to be the source of red meat allergy. In this study, we investigated the presence of α-gal in four tick species: the lone-star tick (Amblyomma americanum), the Gulf-Coast tick (Amblyomma maculatum), the American dog tick (Dermacentor variabilis), and the black-legged tick (Ixodes scapularis) by using a combination of immunoproteomic approach and , carbohydrate analysis., and basophil activation approaches. Using aAnti-α-gal antibodies, α-gal was identified α-gal in the salivary glands of both Am. americanum and Ix. scapularis, while Am. maculatum and De. variabilis appeared to lack the sugarcarbohydrate. PNGase F treatment confirmed the deglycosylation of N-linked α-gal-containing proteins in tick salivary glands. Immunolocalization of α-gal moieties to the salivary secretory vesicles of the salivary acini also confirmed the secretory nature of α-gal-containing antigens in ticks. Am. americanum ticks were fed on human blood (lacks α-gal) using a silicone membrane system to determine the source of the α-gal. N-linked glycan analysis revealed that Am. americanum and Ix. scapularis have α-gal in their saliva and salivary glands, but Am. maculatum contains no detectable quantity. Consistent with the glycan analysis, salivary samples from Am. americanum and Ix. scapularis stimulated activation of basophils primed with plasma from α-gal allergic subjects. Together, these data support the idea that bites from certain tick species may specifically create a risk for the development of α-gal-specific IgE and hypersensitivity reactions in humans. Alpha-Gal syndrome challenges the current food allergy paradigm and broadens opportunities for future research.